Tropical dermatology: viral tropical diseases - Lupi, Omar; Tyring, Stephen K. (Journal of the American Academy of Dermatology, 2003)
Viruses are important pathogens in tropical areas; most of them, especially the tropical hemorrhagic fevers, produce mucocutaneous manifestations. More than any other kind of pathogen, viruses have the possibility for being widespread, since they have a greater probability of mutation than do bacteria, can cross species barriers easily, and infect both human beings and animals in habitats with a great biodiversity. Tropical habitats also have been subject to major ecologic changes in the last few decades, exposing humans to direct contact with these viruses and allowing hemorrhagic fevers due to new emergent viruses such as flaviviruses, filoviruses, arenaviruses, and hantaviruses to become major threats to public health. The collapse of eradication programs in many countries, as well as population increases and ecologic modifications, have led to the spread of dengue and yellow fever to large portions of the world owing to the dissemination of vectors, especially mosquitoes, with broad ecologic ranges. Viruses previously restricted to some geographic areas, such as Rift Valley fever, Crimean-Congo hemorrhagic fever, West Nile fever, and monkeypox are now affecting new countries and populations. Other viruses such as herpes B infection often affect travelers and animal handlers in most parts of the world. Dermatologic lesions occur in all these diseases and can facilitate a rapid diagnosis, leading to control of the virus and helping prevent possible outbreaks.